Value of artery resection in pancreatic cancer surgery - JIANG Kuirong (Linchuang Gandanbing Zazhi, 2016)
Locally advanced pancreatic cancer often invades the surrounding blood vessels. Currently, pancreatectomy combined with venous resection for the treatment of patients with venous involvement is accepted worldwide, but pancreatectomy combined with arterial resection for arterial involvement is still controversial. With reference to the latest research advances at home and abroad and the experience in our center, this article investigates the value of arterial resection in pancreatic cancer surgery, in order to provide a reference for clinical studies